2022
DOI: 10.3389/fonc.2022.922196
|View full text |Cite
|
Sign up to set email alerts
|

Origanum syriacum L. Attenuates the Malignant Phenotype of MDA-MB231 Breast Cancer Cells

Abstract: Breast cancer is the leading cause of cancer-related deaths among women. Among breast cancer types, triple negative breast cancer (TNBC) is the most aggressive, and is resistant to hormonal and chemotherapeutic treatments. As such, alternative approaches that may provide some benefit in fighting this debilitating pathology are critically needed; hence the utilization of herbal medicine. Origanum syriacum L., one of the most regularly consumed plants in the Mediterranean region, exhibits antiproliferative effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…This action maybe mediated by the ZNE-and F6-mediated reduction of integrin-β1 protein levels in TNBC cells. This is in line with other studies which have shown that plants extracts have reduced cell-ECM adhesion and thus inhibited the metastatic potential of TNBC cells (El Hasasna et al, 2016;AlKahlout et al, 2022;Mesmar et al, 2022b). These results invite future investigation of the ability of Z. nummularia to impact other EMT proteins such as E-cadherin, N-cadherin, vimentin, Slug, Snail, and others (Singh and Settleman, 2010;Thiery and Lim, 2013;El-Hajjar et al, 2019;AlKahlout et al, 2022;Mesmar et al, 2022b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This action maybe mediated by the ZNE-and F6-mediated reduction of integrin-β1 protein levels in TNBC cells. This is in line with other studies which have shown that plants extracts have reduced cell-ECM adhesion and thus inhibited the metastatic potential of TNBC cells (El Hasasna et al, 2016;AlKahlout et al, 2022;Mesmar et al, 2022b). These results invite future investigation of the ability of Z. nummularia to impact other EMT proteins such as E-cadherin, N-cadherin, vimentin, Slug, Snail, and others (Singh and Settleman, 2010;Thiery and Lim, 2013;El-Hajjar et al, 2019;AlKahlout et al, 2022;Mesmar et al, 2022b).…”
Section: Discussionsupporting
confidence: 90%
“…It is plausible that inhibition of MMP-9 activity is responsible for the compromised migratory and invasive capabilities induced by ZNE and F6. Other plant extracts have been reported to attenuate the migration and invasion of cancer cells by acting through MMP-2 and MMP-9 reduction (AlKahlout et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased appreciation of medicinal plants and their phytochemicals both in pharmacological studies and drug development programs (Al Dhaheri et al, 2014;El Hasasna et al, 2015;El Hasasna et al, 2016;Athamneh et al, 2017;Alsamri et al, 2019;Badran et al, 2019;Alsamri et al, 2021a;Mesmar et al, 2021;AlKahlout et al, 2022;Alsamri et al, 2022). Approximately, a third of all drugs approved by the Food and Drug Administration (FDA) over the past 20 years have been obtained from or inspired by natural/herbal compounds/derivatives (Izzo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One resource that is bountiful in such compounds is plants. Indeed, natural products from medicinal plants and their constituents serve as a crucial source of bioactives that appear promising to prevent or manage various diseases ( Anwar et al, 2016 ; Anwar et al, 2017 ; Anwar et al, 2018 ; Kim et al, 2018 ; Samaha et al, 2019 ; Fardoun et al, 2020 ; AlKahlout et al, 2022 ). For example, three plants belonging to the genus Verbascum (family Scrophulariaceae), namely, V. cheiranthifolium V. myriocarpum and V. pyroliforme , are rich in phenolics and possess significant antioxidant and enzyme inhibitory activities ( Zengin et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%